The Effectiveness of Kirinyuh (Chromolaena odorata L.) Leaf Essential oil as an Antibacterial Staphylococcus aureus and Escherichia coli - juwairiah juwairiah; Erfan Roebiakto (Baiman Bauntung Batuah Center, 2022)
One of the plants with antibacterial activity is Kirinyuh (Chromolaena odorata L.). The essential oil from these plants has the potential as a natural antibacterial against pathogenic bacteria, such as Staphylococcus aureus and Escherichia coli. This study aims to analyze the antibacterial ability of kirinyuh leaf essential oil (Chromolaena odorata L.) originating from Martapura, Indonesia, by the diffusion method, especially in its ability to inhibit the growth of Staphylococcus aureus and Escherichia coli. The study used five variations of the concentration of essential oils, namely 10 ul, 15 ul, 20 ul, 25 ul, and 30 ul, carried out five times. Essential oil distillation using water and steam distillation method. Antibacterial activity test using well diffusion method. The results showed that the diameter of the inhibition zone against Staphylococcus aureus had a diameter of 9.4mm at a concentration of 10uL, 10.8mm at a concentration of 15uL, 11.6mm at a concentration of 20uL, 13mm at a concentration of 25uL, and 14.4mm at a concentration of 30uL. The diameter of the inhibition zone against Escherichia coli had a diameter of 11.6mm at a concentration of 10uL, 12.8mm at a concentration of 15uL, and 14mm at a concentration of 20uL, 14.8mm at a concentration of 25uL, 15.8mm at a concentration of 30uL. Conclusion The most significant inhibition zone of kirinyuh leaf essential oil (Chromolaena odorata L.) against Staphylococcus aureus was 14.4mm at a concentration of 30uL and against Escherichia coli was 15.8mm at a concentration of 30uL. Further research is needed on the antibacterial effectiveness of kirinyuh leaf essential oil (Chromolaena odorata L.) against other types of bacteria and also against antibiotic-resistant bacteria.